2019
DOI: 10.1002/pd.5559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xylocaine spray for analgesia during amniocentesis: a randomized controlled trial

Abstract: Objective To compare the effect of Xylocaine spray on pain score during amniocentesis Methods Singleton pregnant women undergoing amniocentesis were recruited. Each participant was randomly assigned into three groups. Group 1 (Xylocaine spray): 1 min before the procedure, 8 puffs (80 mg) of 10% Lidocaine spray were sprayed on abdominal wall: group 2 (placebo): 8 puffs of sterile normal saline were sprayed: and group 3 (control): no spray was used. The participants rated their pain through a 10‐cm visual analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Overall, 203 citations were retrieved after the omission of duplicates. Additionally, nine articles progressed to full-text screening, of which five studies met the eligibility criteria and were included in the quantitative synthesis ( Figure 1 ) ( 5 , 6 , 7 , 8 , 9 ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 203 citations were retrieved after the omission of duplicates. Additionally, nine articles progressed to full-text screening, of which five studies met the eligibility criteria and were included in the quantitative synthesis ( Figure 1 ) ( 5 , 6 , 7 , 8 , 9 ) .…”
Section: Resultsmentioning
confidence: 99%
“…We included five RCTs ( 5 , 6 , 7 , 8 , 9 ) with 1004 patients (lidocaine arm n=502 patients and control arm n=502 patients). Three RCTs used lidocaine as injection ( 5 , 6 , 7 ) and two RCTs used it as non-injection [spray ( 8 ) and cream ( 9 ) ]. Table 1 and Table 2 , respectively, summarize the major features of the included studies and participants.…”
Section: Summary Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While pharmacological therapy can be used for local pain control, a study by Pongrowjpaw et al 4 in 2007 found that lidocaine‐prilocaine cream does not decrease the pain during amniocentesis. Use of xylocaine spray 15 does have some pain‐reducing effect, but only when confined to the skin and mucosal layer. Pain reduction was minimal and had only a short duration.…”
Section: Discussionmentioning
confidence: 99%
“…Local lidocaine injection can inhibit nerve conduction at the skin area, subcutaneous tissue, peritoneal, and uterus. This procedure maximizes the analgesic effect during amniocentesis, while the local topical analgesia in the previous studies 4,15,17 can affect the nerve conduction only on the skin, mucosa, and subcutaneous tissue. Furthermore, the local application of analgesia is simple and less painful as compared with analgesia injection, and does not have the risks associated with intravenous lidocaine injection and lidocaine hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%